Exploring The Experiences Of Sexual Abuse Victims In The Forensic Examination Process At The Rejang Lebong Regional Public Health Facility - Nova Kristi Fransiska; Herlita Eryke; Marliz Tarmizi (Journal of Law, Politic and Humanities, 2026)
This study examines the experiences of child and adolescent sexual abuse victims during the forensic examination process at health facilities in Rejang Lebong. Sexual violence against children is a serious and complex problem that requires a multidisciplinary approach to its handling. Based on in-depth interviews and prior literature, it was found that the forensic examination process frequently causes deep psychological trauma to victims, particularly when procedures are conducted invasively and without adequate empathy. Many victims reported feeling afraid, anxious, and disrespected, especially when officers failed to apply a trauma-informed approach or to maintain their privacy. Their experiences highlight the critical need for humane services characterized by empathetic communication and comfortable, safe facilities. The findings indicate that conducting examinations in a sensitive, transparent manner that respects human rights is essential for reducing ongoing trauma and strengthening victims' trust in the legal system and healthcare services. Trauma-informed care approaches, continuous training for personnel, and improvements to facilities and awareness of victims' rights are proposed as principal strategies to ensure that the forensic process is conducted humanely and effectively. Overall, this study underscores the importance of a trauma-informed approach within the healthcare system and law enforcement to protect the human rights of victims and minimize the long-term effects of trauma